Association between infection with Helicobacter pylori and atopy in young Ethiopian children: A longitudinal study. Issue 10 (4th September 2017) - Taye, B.; Enquselassie, F.; Tsegaye, A.; Amberbir, A.; Medhin, G.; Fogarty, A.; Robinson, K.; Davey, G.
Summary: Background: Epidemiological evidence from developed countries indicates that Helicobacter pylori infection correlates with a reduced risk of atopy and allergic disorders; however, limited data are available from low‐income countries. Objective: We examined associations between H. pylori infection in early childhood and atopy and reported allergic disorders at the age of 6.5 years in an Ethiopian birth cohort. Methods: A total of 856 children (85.1% of the 1006 original singletons in a population‐based birth cohort) were followed up at age six and half years. An interviewer‐led questionnaire administered to mothers provided information on demographic and lifestyle variables. Questions on allergic disease symptoms were based on the International Study of Asthma and Allergies in Children (ISAAC) core allergy and environmental questionnaire. Serum samples were analysed for total IgE levels and anti‐ H. pylori cytotoxin‐associated gene A (CagA) IgG antibody using commercially available ELISA kits. Stool samples were analysed for H. pylori antigen using a rapid immunochromatographic test. The independent effects of H. pylori infection (measured at age of 3, 5 and 6.5 years) on prevalence and incidence of atopy and reported allergic disorders (measured at age of 6.5 years) were determined using multiple logistic regression. Results: In cross‐sectional analysis, current H. pylori infection at age 6.5 years was inversely, though not significantly, related to prevalence of atopy and "any allergic condition" at age 6.5 years. However, detection of H. pylori infection at any point up to age 6.5 years was associated with a significantly reduced odds of both atopy and "any allergic condition" (adjusted OR AOR, 95% CI, 0.54; 0.32‐0.92, P  = .02, and .31; 0.10‐0.94, P  = .04, respectively). In longitudinal analyses, H. pylori infection at age 3 was inversely associated with incidence of atopy (AOR, 95% CI, 0.49; 0.27‐0.89, P  = .02). Furthermore, among H. pylori ‐infected children, those with a CagA+ strain had a more pronounced reduction in odds of atopy (AOR = 0.35 vs 0.63 for CagA+ vs CagA‐), and this reduction reached borderline significance. Conclusion: These data are consistent with the hypothesis that early exposure to H. pylori is inversely associated with atopy and allergic conditions. A possible modest protective association against atopy was observed in those infected with a more virulent CagA+ strain of H. pylori .